2004
DOI: 10.1021/ac0493166
|View full text |Cite
|
Sign up to set email alerts
|

Assignment and Quantification of 2-Aminopyridine Derivatized Oligosaccharide Isomers Coeluted on Reversed-Phase HPLC/MS by MSn Spectral Library

Abstract: 2-Aminopyridine (PA)-derivatized oligosaccharides from IgG were analyzed by using reversed-phase HPLC/mass spectrometry (RP-HPLC/MS) and a MS(n) spectral library, in particular, focusing on two pairs of isomers incompletely separated or coeluted in chromatograms. We previously reported that MS(n) spectral matching considering both major fragment ions (m/z) and intensities is useful and applicable to the structural assignment of PA-oligosaccharide isomers. In this study, MS(n) spectral matching based on the MS(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…It was observed that compounds closely related structurally consisting of anomers and linkage isomers could be distinguished by CID spectra when multiple ions were obtained. This indicates that the spectral differences often observed for isomeric natural oligosaccharides are not just a coincidence, and also supports the usefulness of methods based on spectral matching [11][12][13][14][15][16][17]. A problem, however, is that this is true only when a sufficient number of distinct signals were collected for the comparison.…”
Section: Cid Analysis Of All Compoundssupporting
confidence: 59%
See 1 more Smart Citation
“…It was observed that compounds closely related structurally consisting of anomers and linkage isomers could be distinguished by CID spectra when multiple ions were obtained. This indicates that the spectral differences often observed for isomeric natural oligosaccharides are not just a coincidence, and also supports the usefulness of methods based on spectral matching [11][12][13][14][15][16][17]. A problem, however, is that this is true only when a sufficient number of distinct signals were collected for the comparison.…”
Section: Cid Analysis Of All Compoundssupporting
confidence: 59%
“…In most cases, there are differences in signal intensities, whereas in others, different fragment ions can be found. Accumulation of the spectral data in a database facilitates identification of oligosaccharides based on spectral matching [11][12][13][14][15][16][17]. An important problem-the elucidation of totally unknown structures that are not present in any databasewill still remain after the introduction of this efficient methodology.…”
mentioning
confidence: 99%
“…Following improvements in sensitivity or resolution, the method utilized here is applicable to other disease or oligosaccharide alterations. SSI-IT/MS can also be used to analyze sialyl oligosaccharides and distinguish isomers using MS n [12,13]; thus a combination of SSI-IT/MS and RP-HPLC should be widely applicable to N-glycan analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Sonic spray ionization ion trap mass spectrometry (SSI-IT/MS) ionizes mildly with nitrogen 4 gas flow [12] and is applicable to quantitative analysis of neutral and sialic oligosaccharides in the negative ion mode [13,14]. Thus we combined SSI-IT and MS in order to compare N-glycan profiles from whole sera of healthy women and female RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Weiskopf et al also demonstrated that the core pentasaccharide structure generated from a sialylated and an asialyl-N-glycan exhibit a similar fragment pattern in their MS 4 and MS 3 spectra (referred to as``MS nˆn gerprinting'') (28). The MS n spectral library methods for pyridylamino (PA) N-glycans proposed by Takegawa et al (30,31) and by Kameyama et al (7,32,33) also fall into this category. All of these similar approaches can be considered as versions of``MS n spectral matching.''…”
Section: B Ms-based Structural Analysis Of Glycansmentioning
confidence: 98%